Integral Sliding Mode Control of a Single-Phase Current-Source Inverter - Komurcugil, Hasan (IEEE, 2009)
Two current-control strategies based on the sliding mode concept have been introduced for a single-phase current-source inverter feeding a resistive load. The first strategy is based on forming a general switching function using the error variables of the inductor current and capacitor voltage. However, it is observed that this control strategy leads to a steady-state error in the capacitor voltage. In order to reduce this steady-state error, the second strategy using an additional integral term of the error variables in the switching function is proposed. It is observed that the additional integral term alleviates the steady-state error in the capacitor voltage. The existence conditions for stability are determined for both control strategies. Simulations and experiments are carried out to confirm the effectiveness of proposed control strategies.
35th Annual Conference of the IEEE-Industrial-Electronics-Society -- NOV 03-05, 2009 -- Porto, PORTUGAL
Keywords: Voltage-Source; Drive System